Islamic educational leadership strategy planning in optimizing the education budget at SDN 20 Timbulun - Nanda, Septia Irnanda; Irawadi, Hermen; Asmendri, Asmendri; Sari, Milya (Indonesia Accounting Research Journal, 2024)
This study aims to analyze the strategic planning of Islamic educational leadership in optimizing the education budget at SDN 20 Timbulun. In the midst of limited allocated education budget, the principal and stakeholders have a crucial role in managing resources in order to support the achievement of educational goals. A leadership approach based on Islamic values ​​is expected to guide fair, transparent, and efficient decision-making. This study uses a qualitative method with in-depth interviews and observations of principals, teachers, and other related parties. The results of the study indicate that strategic planning that integrates Islamic leadership principles, such as deliberation, justice, and trustworthiness, can increase the effectiveness of budget management. Optimal budget utilization is achieved through mapping priority needs, strict supervision of budget use, and strong collaboration between stakeholders. This study recommends the importance of increasing the leadership capacity of principals in the aspects of planning and managing budgets based on Islamic values ​​to achieve quality education.